2013
DOI: 10.1007/s11030-013-9459-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of spiro[indoline-3,1 $$^\prime $$ ′ -quinolizines] and spiro[indoline-3,4 $$^\prime $$ ′ -pyrido[1,2-a]quinolines] via three-component reactions of azaarenes, acetylenedicarboxylate, and 3-methyleneoxindoles

Abstract: The three-component reactions of substituted pyridines, dimethyl acetylenedicarboxylates, and 3-phenacylideneoxindoles afforded spiro[indoline-3,1-quinolizines] in high yields and with high diastereoselectivity. The Diels–Alder reactions of spiro[indoline-3,1-quinolizines] with maleic anhydride and -phenyl maleimides successfully resulted in polyfunctionalized isoquinolinuclidine derivatives. The similar three-component reactions with quinoline resulted in the novel spiro[indoline-3,4-pyrido[1,2-a]quinolines] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…However no dr ratio was mentioned (scheme 20B). 77 Shi and co-workers have reported a three-component condensation of a pyridine, an acetylenedicarboxylates, and an N-substituted isatylidene to afford the spiro[indoline-3,3- piperidin]-2-one skeleton 96 under mild reaction conditions (Scheme 20C). 78 A variety of 1,9adihydrospiro[indoline-3,2-quinolizin]-2-one derivatives 96 were obtained in moderate to excellent yields (53-99%) and with good to excellent dr values (up to 99:1).…”
Section: Dearomatizing [M + N] Cycloaddition Reactionsmentioning
confidence: 99%
“…However no dr ratio was mentioned (scheme 20B). 77 Shi and co-workers have reported a three-component condensation of a pyridine, an acetylenedicarboxylates, and an N-substituted isatylidene to afford the spiro[indoline-3,3- piperidin]-2-one skeleton 96 under mild reaction conditions (Scheme 20C). 78 A variety of 1,9adihydrospiro[indoline-3,2-quinolizin]-2-one derivatives 96 were obtained in moderate to excellent yields (53-99%) and with good to excellent dr values (up to 99:1).…”
Section: Dearomatizing [M + N] Cycloaddition Reactionsmentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35][36][37][38][39][40] Recently, we successfully found that spiro[indoline-3,1'-quinolizin]-2-ones, which were generated from the three-component reaction of substituted pyridine, acetylenedicarboxylate and 3-phenacylideneoxindoles, could undergo Diels-Alder reaction with the typical dienophiles such as maleic anhydride and N-phenylmaleimides. [41][42][43] Alternatively, spiro[3H-indole-3,2'-[2H,9aH-pyrido [2,1-b] [1,3]oxazine], which were formed from three-component reaction of the substituted pyridines, electron-deficient alkynes and isatins, also underwent Diels-Alder reaction with 3-phenacylideneoxindoles (eq. 1 in Scheme 1).…”
Section: Introductionmentioning
confidence: 99%